PENGARUH METODE BELAJAR SAMBIL BERMAIN DENGAN MEDIA PUZZLE PADA PEMBELAJARAN PPKn UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF SISWA KELAS IV SDN 07 KOTA BIMA - Taufiqurahman; Ihsan; Miftahul Jannah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study employed a quasi-experimental method involving two groups, namely an experimental class and a control class. The purpose of the study was to determine the effect of the treatment given to the research subjects. Data analysis was conducted using IBM SPSS Statistics 24. The normality test showed significance values (Sig) for both classes greater than 0.05, indicating that the data were normally distributed. The homogeneity test also showed significance values greater than 0.05, indicating that the students' PPKn learning outcomes had homogeneous variances. Furthermore, the t-test revealed a significance value of 0.000 < 0.05, leading to the conclusion that H₀ is rejected and Hₐ is accepted. Therefore, the implementation of the play-based learning method using puzzle media was proven effective in enhancing the creative thinking skills of fourth-grade students at SDN 07 Kota Bima.